Pengalaman Akulturasi dan Resolusi Konflik Warga Keturunan Tionghoa di Semarang - Slamet Subekti (Endogami: Jurnal Ilmiah Kajian Antropologi, 2019)
This case study seeks to reveal the acculturation experience some residents Chinese descent in Semarang. The data collection is done by conducting in-depth interviews with three informants selected, complemented by interviews with a priest in order to gain insights into conflict resolution within the framework of multiculturalism. Key to conflict resolution is the synergic cooperation between the government, security, local religious and tribal leaders. Acculturation as a method of receiving and cultural assimilation became one of alternative conflict prevention. The informant chose multiculturalism as a strategy of acculturation. Communication patterns are tolerant and philosophical values of Pancasila should be developed and cultivated to realize multiculturalism.